Optimization and Reproducibility of Aortic Valve 18F-Fluoride Positron Emission Tomography in Patients With Aortic Stenosis. (October 2016) - Pawade, Tania A.; Cartlidge, Timothy R.G.; Jenkins, William S.A.; Adamson, Philip D.; Robson, Phillip; Lucatelli, Christophe; Van Beek, Edwin J.R.; Prendergast, Bernard; Denison, Alan R.; Forsyth, Laura; Rudd, James H.F.; Fayad, Zahi A.; et al.
Abstract : Background—: 18F-Fluoride positron emission tomography (PET) and computed tomography (CT) can measure disease activity and progression in aortic stenosis. Our objectives were to optimize the methodology, analysis, and scan–rescan reproducibility of aortic valve 18F-fluoride PET-CT imaging. Methods and Results—: Fifteen patients with aortic stenosis underwent repeated 18F-fluoride PET-CT. We compared nongated PET and noncontrast CT, with a modified approach that incorporated contrast CT and ECG-gated PET. We explored a range of image analysis techniques, including estimation of blood-pool activity at differing vascular sites and a most diseased segment approach. Contrast-enhanced ECG-gated PET-CT permitted localization of 18F-fluoride uptake to individual valve leaflets. Uptake was most commonly observed at sites of maximal mechanical stress: the leaflet tips and the commissures. Scan–rescan reproducibility was markedly improved using enhanced analysis techniques leading to a reduction in percentage error from ±63% to ±10% (tissue to background ratio MDS mean of 1.55, bias −0.05, limits of agreement −0·20 to +0·11). Conclusions—: Optimized 18F-fluoride PET-CT allows reproducible localization of calcification activity to different regions of the aortic valve leaflet and commonly to areas of increased mechanical stress. This technique holds major promise in improving our understanding of the pathophysiology of aortic stenosis and as a biomarker end point in clinical trials of novel therapies. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02132026. Abstract : Supplemental Digital Content is available in the text.